Globalization and the Least Developed Countries: Potentials and Pitfalls - Bigman, David (CABI, 2014)
An analysis of the world poverty problem, the policy options to reduce poverty and the stumbling blocks that prevent countries to achieve this goal must therefore focus first and foremost on the LDCs. This is also why in this book I have elected to narrow down the analysis from a general analysis of global poverty to a more focused analysis of poverty in the LDCs. At the same time, I expanded the scope of the analysis in order to highlight the wider problems that these countries are facing, examined the impact of globalization on their economies and evaluated their policy options and the obstacles that they must overcome in order to reduce their poverty in the coming decade